MiR-196b Promotes the Invasion and Migration of Lung Adenocarcinoma Cells by Targeting AQP4 - Wu, Xuhui (Technol Cancer Res Treat, 2021)
OBJECTIVE: We aimed to investigate the mechanism of the regulatory axis of miR-196b/AQP4 underlying the invasion and migration of lung adenocarcinoma (LUAD) cells. METHODS: LUAD miRNA and mRNA expression profiles were downloaded from TCGA database and then differential analysis was used to identify the target miRNA. Target gene for the miRNA was obtained via prediction using 3 bioinformatics databases and intersection with the differentially expressed mRNAs searched from TCGA-LUAD. Then, qRT-PCR and western blot were used to validate the expression of miR-196b and AQP4. Dual-luciferase reporter assay was performed to confirm the targeting relationship between miR-196b and AQP4. Transwell assay was used to investigate the migration and invasion of LUAD cells. RESULTS: MiR-196b was screened out by differential and survival analyses, and the downstream target gene AQP4 was identified. In LUAD, miR-196b was highly expressed while AQP4 was poorly expressed. Besides, overexpression of miR-196b promoted cell invasion and migration, while overexpression of AQP4 had negative effects. Moreover, the results of the dual-luciferase reporter assay suggested that AQP4 was a direct target of miR-196b. In addition, we also found that overexpressing AQP4 could suppress the promotive effect of miR-196b on cancer cell invasion and migration. CONCLUSION: MiR-196b promotes the invasion and migration of LUAD cells by down-regulating AQP4, which helps us find new molecular targeted therapies for LUAD.